Blindfolded vs. informed ultimatum bargaining: A theoretical and experimental analysis - Werner Güth; Kerstin Pull; Manfred Stadler; Alexandra Zaby (University of Tübingen, Faculty of Economics and Social Sciences, 2016)
This paper analyzes blindfolded versus informed ultimatum bargaining where proposer and responder are both either uninformed or informed about the size of the pie. Analyzing the transition from one information setting to the other suggests that more information induces lower (higher) price offers and acceptance thresholds when the pie is small (large). While our experimental data confirm this transition effect, risk aversion leads to diverging results in blindfolded ultimatum bargaining due to task-independent strategies such as 'equal sharing' or the 'golden mean.' The probability of successful bargaining is lower in case of blindfolded than informed ultimatum bargaining.
urn:nbn:de:bsz:21-dspace-694705
Keywords: C91; D82; 330; ultimatum bargaining; information structure; experimental economics